"Quem vai organizar?-- ainda não entrou na minha cabeça!" :etnografando o carnaval de congo de máscaras de Roda D'Água/Cariacica (ES) - Silva, Nathália Brunet Procópio da (2018)
The objective of this dissertation was that of understanding how strategies and tactics are articulated in congo’s spatial organization at “Congo de Máscaras” Carnival. This Carnival is a secular party, originated from the Brazilian slavery context. Today